Knowledge domain and emerging trends in Alzheimer's disease: a scientometric review based on CiteSpace analysis - Liu, Shuo; Sun, Ya-Ping; Gao, Xu-Ling; Sui, Yi (Neural regeneration research, 2019)
Alzheimer's disease is the most common cause of dementia. It is an increasingly serious global health problem and has a significant impact on individuals and society. However, the precise cause of Alzheimer's disease is still unknown. In this study, 11,748 Web-of-Science-indexed manuscripts regarding Alzheimer's disease, all published from 2015 to 2019, and their 693,938 references were analyzed. A document co-citation network map was drawn using CiteSpace software. Research frontiers and development trends were determined by retrieving subject headings with apparent changing word frequency trends, which can be used to forecast future research developments in Alzheimer's disease.